Study of posttranslational non-enzymatic modifications of collagen using capillary electrophoresis/mass spectrometry and high performance liquid chromatography/mass spectrometry - Mikulíková, Katerina; Eckhardt, Adam; Pataridis, Statis; Miksík, Ivan (Journal of chromatography. A, 2007)
The depository effects that occur in slowly metabolized proteins (typically glycation) are very difficult to assess, owing to their extremely low concentration in the protein matrix. Collagen accumulates reactive metabolites through reactions that are not regulated by enzymes. A typical example of these non-enzymatic changes is glycation (the Maillard reaction, the formation of advanced glycation end products), resulting from the reaction of the oxo-group of sugars with the epsilon-amino group of lysine and arginine. Collagen samples (type I) as a test protein were incubated separately with glucose, ribose and malondialdehyde. Collagen was fragmented with cyanogen bromide and then digested with trypsin. This peptide digest was separated by CE, CE-MS/MS, and HPLC-MS/MS. An ion trap MS was used and MS conditions were optimized for both methods. These on-line CE-MS/MS and HPLC-MS/MS couplings made it possible to discover specific modifications such as (N(epsilon)-(carboxymethyl)-lysine) in the precise location in the structure of collagen corresponding to posttranslational non-enzymatic modifications. A new CE-MS/MS technique for peptide analysis was developed, and applied in the identification of posttranslational modifications in slowly metabolized test proteins.
Keywords: Electrophoresis, Capillary; elektroforéza kapilární; Chromatography, High Pressure Liquid; Peptides; produkty pokročilé glykace; Glycation End Products, Advanced; hmotnostní spektrometrie; kolagen; vysokoúčinná kapalinová chromatografie; Protein Processing, Post-Translational; posttranslační úpravy proteinů; Collagen; Mass Spectrometry; peptidy